1996
DOI: 10.1139/v96-025
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of tosylhydrazones of benzoin, benzoin acetate, and benzoin benzoate with alkali and metal complex hydrides

Abstract: Treatment of tosylhydrazones of benzoin, benzoin acetate, and benzoin benzoate with alkali under protic and aprotic conditions yielded diphenyl acetylene together with desoxybenzoin. An increase in leaving aptitude of the adjacent group enhanced the formation of diphenyl acetylene. By treatment with LiAIH, and with NaBH,, the tosylhydrazones gave stilbenes in good yields. Selective formation of cis-or trnns-stilbene was observed in some cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…There are a just a handful of reports of the preparation of acyclic α-alkoxy sulfonyl or acyl , hydrazones from ketones, and only a few that report the hydrazone E/Z -configurations. Alami et al reported a 1.5–5.7:1 Z:E ratio of hydrazones 15 depending upon the identity of R 1 and R 2 (Figure ). The hydrazones were prepared by stirring the ketones with TsNHNH 2 in methanol at ambient temperature.…”
Section: Resultsmentioning
confidence: 99%
“…There are a just a handful of reports of the preparation of acyclic α-alkoxy sulfonyl or acyl , hydrazones from ketones, and only a few that report the hydrazone E/Z -configurations. Alami et al reported a 1.5–5.7:1 Z:E ratio of hydrazones 15 depending upon the identity of R 1 and R 2 (Figure ). The hydrazones were prepared by stirring the ketones with TsNHNH 2 in methanol at ambient temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Also, photochemical decomposition of benzocyclobutenone p-toluenesulfonylhydrazone led to E-and Z-isomers of 1,1-bi(benzocyclobutenylidenes) as the major products in addition to a wide variety of products [4]. Furthermore, it has been reported that the decomposition of tosylhydrazones of benzoin and benzoin acetate and benzoin benzoate under protic and aprotic conditions with alkali yielded diphenyl acetylene together with deoxybenzoin by an obscure mechanism [5]. This finding prompted us to reinvestigate of thermolysis of these compounds to gain further insight into the mechanism of fragmentation.…”
Section: Introductionmentioning
confidence: 99%